Usage of BIM for Improvement on Design Coordination in Construction Industry - Tan , Yee Ling; Mohamed, Sulzakimin; Adejoh Ahmodu , Adaji (Research in Management of Technology and Business, 2024)
Nowadays, Building Information System (BIM) is one of the most exciting developments in the Architectural, Engineering, and Construction (AEC) sector. However, there is a lack in using BIM in construction industry in Malaysia. The objectives of this research are to study on the improvement that BIM can do for design coordination in construction industry, study the benefits of BIM coordination for future development and investigate the strategy of BIM’s improving coordination in construction project among project managers in Kuala Lumpur. This study is conducted in Selangor and Kuala Lumpur area of Malaysia. The methodology of this study included interview and gathered information and data from articles, news, and related journals. A total of 3 respondent are interviewed in order to gain deeper insight needed for the purpose of this research objectives. The analysis of data shows that the benefits and strategy of BIM in the construction industry are well and truly existed. Most of the respondent stated that clash detection, communication and 3D models can improve the communication. Moreover, the reduce reworks and visualize can brought the benefits of communication. In addition, adoption and integration and collaboration and communication have brought the strategy of communication. These bring benefit and strategy of BIM by providing construction industry to improve design coordination.